Effect of feeding practices and manure quality on CH4 and N2O emissions from uncovered cattle manure heaps in Kenya. (1st May 2021) - Leitner, Sonja; Ring, Dónal; Wanyama, George N.; Korir, Daniel; Pelster, David E.; Goopy, John P.; Butterbach-Bahl, Klaus; Merbold, Lutz
Highlights: CH4 and N2 O emissions from cattle manure heaps in Kenya were measured. Cattle had either restricted feed intake or received poor-quality forage grass. Low manure N concentration and high C:N ratio reduced N2 O emissions. N2 O emission factors were similar to or lower than the IPCC default for solid storage. CH4 emission factors were similar to or lower than IPCC default values. Abstract: Countries in sub-Saharan Africa (SSA) rely on IPCC emission factors (EF) for GHG emission reporting. However, these were derived for industrialized livestock farms and do not represent conditions of smallholder farms (small, low-producing livestock breeds, poor feed quality, feed scarcity). Here, we present the first measurements of CH4 and N2 O emissions from cattle-manure heaps representing feeding practices typical for smallholder farms in the highlands of East Africa: 1) cattle fed below maintenance energy requirements to represent feed scarcity, and 2) cattle fed tropical forage grasses (Napier, Rhodes, Brachiaria). Sub-maintenance feeding reduced cumulative manure N2 O emissions compared to cattle receiving sufficient feed but did not change EFN2O . Sub-maintenance feeding did not affect cumulative manure CH4 emissions or EFCH4 . When cattle were fed tropical forage grasses, cumulative manure N2 O emissions did not differ between diets, but manure EFN2O from Brachiaria and Rhodes diets were lower than the IPCC EFN2O for solid storage (1%, 2019 Refinement of IPCC Guidelines). Manure CH4 emissions were lower in the Rhodes grass diet than when feeding Napier or Brachiaria, and manure EFCH4 from all three grasses were lower than the IPCC default (4.4 g CH4  kg −1 VS, 2019 Refinement of IPCC Guidelines). Regression analysis revealed that manure N concentration and C:N were important drivers of N2 O emissions, with low N concentrations and high C:N reducing N2 O emissions. Our results show that IPCC EFs overestimate excreta GHG emissions, which calls for additional measurements to develop localized EFs for smallholder livestock systems in SSA.